2021
DOI: 10.1038/s41467-021-24909-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing activity of Sputnik V vaccine sera against SARS-CoV-2 variants

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected at least 180 million people since its identification as the cause of the current COVID-19 pandemic. The rapid pace of vaccine development has resulted in multiple vaccines already in use worldwide. The contemporaneous emergence of SARS-CoV-2 ‘variants of concern’ (VOC) across diverse geographic locales underscores the need to monitor the efficacy of vaccines being administered globally. All WHO designated VOC carry spike (S) polymorphism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 79 publications
4
65
2
6
Order By: Relevance
“…A small, independent Argentinean study by Ikegame and colleagues has shed light on this fundamental aspect revealing the worrying possibility that the Beta variant, and to a lesser extent, any variant carrying the E484K substitution may escape the neutralising antibody responses that this immunisation elicits [ 38 , 39 ]. The important information is that 8 out of 12 (67%) serum samples from a cohort of recipients of Sputnik V vaccine showed dose response curve slopes indicative of failure to neutralize Beta variant, but antibodies from people who had received both doses of Sputnik V were effective against the Alpha variant and D614G variant and showed only moderately reduced activity against S carrying the E484K substitution alone.…”
Section: Consmentioning
confidence: 99%
“…A small, independent Argentinean study by Ikegame and colleagues has shed light on this fundamental aspect revealing the worrying possibility that the Beta variant, and to a lesser extent, any variant carrying the E484K substitution may escape the neutralising antibody responses that this immunisation elicits [ 38 , 39 ]. The important information is that 8 out of 12 (67%) serum samples from a cohort of recipients of Sputnik V vaccine showed dose response curve slopes indicative of failure to neutralize Beta variant, but antibodies from people who had received both doses of Sputnik V were effective against the Alpha variant and D614G variant and showed only moderately reduced activity against S carrying the E484K substitution alone.…”
Section: Consmentioning
confidence: 99%
“…Research has shown vaccine efficacy (two doses) against the alpha variant to be 74.5% with the Oxford-AstraZeneca vaccine, 93.7% with the Pfizer-BioNTech vaccine,2 85.6% with the Novavax vaccine,3 and 100% with the Moderna vaccine 4. A study looking at the Sputnik V vaccine saw some reduced neutralising activity against the alpha variant,5 and Thailand’s Public Health Ministry has reported that two doses of the Sinovac vaccine are 71-91% effective against alpha 6. (Video 1)…”
Section: Alphamentioning
confidence: 99%
“…Sputnik V’s maker claims that it is “highly effective” against beta, but at least one study has noted a reduction in neutralising activity against this variant 5. Data on the efficacy of Sinovac’s CoronaVac are lacking, although reports from Hong Kong suggested that the level of protection was 70% lower against beta than against wild-type 9…”
Section: Betamentioning
confidence: 99%
“…In this design, 2P mutations (K986P and V987P) are introduced in spike protein to stabilize it in a prefusion trimeric conformation. Interestingly, vaccines that did not use 2P stabilized spike antigen appear to generate a more variable neutralizing response, which makes it difficult to establish a protective immune response against emerging SARS-CoV-2 variants [ 17 , 18 ].…”
Section: P Approach In Covid-19 Vaccine Designmentioning
confidence: 99%